Analisis Perbandingan Kinerja Keuangan PT. Bank Mandiri (Indonesia) Dan Malayan Bank Bhd (Malaysia) Periode Tahun 2013-2017 - Samsul Hadi; Phonny Aditiawan Mulyana; Budi Wahyu Mahardhika (BALANCE: Economic, Business, Management and Accounting Journal, 2019)
ABSTRACT  Banking is a financial institution that has a very important role in economic and business activities. Lending activities and services rendered by banks in trade and economic activity can move country’s economy. Their banking companies will assist communities in improving their quality of life and may help the government in solving the economic problems that occur in a country.This study aimes to analyze the financial performance at PT. Bank Mandiri (Indonesia) and Malayan Bank Bhd (Malaysia) by using descriptive analysis with analysis tools and test different financial ratios Independent Samples T-Test. The results showed there are differences between the financial performance of the Bank and Malayan Bank (Maybank) in ROA, BOPO, LDR and ROE. As for the CAR and NPM there are differences in financial performance. Maybank management should pay more attention improve its financial performance. Likewise for the Management of the Bank is expected to maintain current excellent financial performance.Keywords                   : financial performance, financial ratiosCorrespondence to       : budi.w.mahardhika@gmail.com ABSTRAK              Perbankan merupakan lembaga keuangan yang sangat penting peranannya dalam kegiatan ekonomi dan bisnis. Kegiatan perkreditan dan jasa yang diberikan oleh perbankan dalam kegiatan perdagangan dan aktivitas ekonomi dapat menggerakkan perekonomian suatu negara. Adanya perusahaan perbankan akan membantu masyarakat dalam meningkatkan taraf hidupnya dan dapat membantu pemerintah dalam menyelesaikan masalah perekonomian yang terjadi pada suatu negara.Penelitian ini bertujuan untuk menganalisis kinerja keuangan pada PT. Bank Mandiri (Indonesia) dan Malayan Bank Bhd (Malaysia) dengan menggunakan metode analisis deskriptif dengan alat analisis rasio keuangan dan uji beda Independent Sampel T Test. Hasil penelitian menunjukan terdapat perbedaan kinerja keuangan antara Bank Mandiri dan Malayan Bank (MayBank) dalam rasio ROA, BOPO, LDR dan ROE. Sedangkan untuk rasio CAR dan NPM tidak terdapat perbedaan kinerja keuangan. Manajemen MayBank harus lebih memperhatikan serta meningkatkan kinerja keuangannya. Begitu juga untuk Manajemen Bank Mandiri diharapkan tetap mempertahankan kinerja keuangannya yang sudah baik.Kata kunci                  : kinerja keuangan, rasio keuanganKorespondensi             :  budi.w.mahardhika@gmail.com